PROSPEK PENERAPAN SISTEM CORPORATE FARMING - Dalimunthe, Iqbal Musthofa; Kurnia, Ganjar (Jurnal AGRISEP, 2018)
Corporate farming is a farmland merger activity that is organized together by farmers in an integrated single management. This system could be a solution for many problems facedby farmerstoday, such asbusiness efficiency, quality standardization, and effectivenessas well as input use efficiency.Gerbang Emas Agricultural Cooperative is a farmer’s business organization focusing on the production and marketing of horticultural crops. The cooperative has implemented the collective marketing since 2014, but the production is carried out individually by the farmers. Low level of productivity is the problem the cooperative faced. The farming activities that are currently done by the farmers would be more efficient if managed by implementing the corporate farming system. The purpose of this study is to analyze the prospect for the implementation of corporate farming system and also to determine the factors affecting the likelihood of success or failure in the system implementation at Gerbang Emas Agricultural Cooperative. The research method used is the descriptive method, analyzing the prospect from three perspectives (economic, institutional, and social). The result shows that the corporate farming system has a good prospect to be implemented on the cooperative, viewed from all perspectives. In addition, this study also obtained several factors that affect the likelihood of success or failure in the implementation of the system on the cooperative namely: 1)Integration of corporate farming development with local economic development,2)Availability of capable institutions (government / non-government) of functioning as a facilitator, 3)Emotional and cultural ties between the farmer and his land, 4)Differenceperceptions among farmers, 5)Deferentin the development of agribusiness system.